WORKLOAD AND UNIVERSAL PRECAUTIONS COMPLIANCE AMONG HEALTH WORKERS IN AN EMERGENCY ROOMS - Novi Tiara; Diah Irawati; Umi Faridah; Muhamad Jauhar ((IJP) Indonesia Jurnal Perawat, 2024)
Healthcare-associated infections (HAIs) are prevalent in nearly all healthcare facilities worldwide. The most effective way to prevent these infections is to implement universal precautions during patient care in hospitals consistently. In Indonesia, the reported incidence of HAIs is significantly higher than the rates in developed countries. Several risk factors influence the occurrence of HAIs, including advanced age, compromised immune systems, disruptions to anatomical barriers, the presence of implanted foreign objects, and changes in normal microflora caused by antibiotic use. If not addressed promptly, non-compliance with Universal Precautions can lead to various adverse outcomes for patients, including potential disability or even death. This research aims to analyze the relationship between workload and compliance with the implementation of Universal Precautions among healthcare workers. The study used an analytic correlation design with a cross-sectional approach, targeting healthcare staff working in the Emergency Department of Bhakti Wira Tamtama Hospital in Semarang, totaling 33 participants. A total sampling technique was used for participant selection. The research utilized a workload questionnaire and an observation sheet for Universal Precaution compliance. Data analysis using the Chi-Square test revealed a significant relationship between workload and compliance with Universal Precautions among healthcare workers, with a p-value of 0.000 (p0.05). The findings of this study highlight the importance of providing additional education for healthcare workers who have limited knowledge and awareness of Universal Precautions to enhance compliance and reduce the incidence of HAIs.